2010
DOI: 10.1021/jf100700p
|View full text |Cite
|
Sign up to set email alerts
|

Release of Bound Procyanidins from Cranberry Pomace by Alkaline Hydrolysis

Abstract: Procyanidins in plant products are present as extractable or unextractable/bound forms. We optimized alkaline hydrolysis conditions to liberate procyanidins and depolymerize polymers from dried cranberry pomace. Alkaline extracts were neutralized (pH 6-7) and then procyanidins were extracted with ethyl acetate and analyzed by normal phase high performance liquid chromatography. Alkaline hydrolysis resulted in an increase in low molecular weight procyanidins, and the increase was greater at higher temperature, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(81 citation statements)
references
References 32 publications
(53 reference statements)
3
73
0
3
Order By: Relevance
“…3,7,8 Consequently, the phenolics content in any analytical determination is underestimated because of the bound phenolic cell-wall material that is not released by normal extraction protocols. To liberate bound phenolic derivatives, acid or base hydrolysis is applied to the plant sample prior to conventional extraction or to residual sediments resulting from conventional extraction procedures.…”
Section: Hclmentioning
confidence: 99%
See 1 more Smart Citation
“…3,7,8 Consequently, the phenolics content in any analytical determination is underestimated because of the bound phenolic cell-wall material that is not released by normal extraction protocols. To liberate bound phenolic derivatives, acid or base hydrolysis is applied to the plant sample prior to conventional extraction or to residual sediments resulting from conventional extraction procedures.…”
Section: Hclmentioning
confidence: 99%
“…5:2.5, v/v) and FeCl 3 at 100°C for 1 h. Furthermore, to liberate bound PAC derivatives, base hydrolysis was employed to treat cranberry pomace prior to conventional extraction protocols. 8 Caution must be exercised because severe alkaline conditions can, nonetheless, lead to cleavage of C−C interflavan bonds between the monomeric flavan-3-ol constituents. This may explain why alkalinehydrolyzed PACs typically exist as monomers, dimers, trimers, and other low-molecular-weight oligomers.…”
Section: Hclmentioning
confidence: 99%
“…Recent studies have clearly indicated the potential of incorporating various fruit and vegetable-based pomace in extruded products like apple pomace (Alavi et al, 2011;Karkle et al, 2012), grape pomace (Altan et al, 2008;Kumar et al, 2010), cranberry pomace (White et al, 2010), blue berry pomace (Khanal et al, 2009), tomato pomace (Altan et al, 2008), and carrot pomace (Altan et al, 2008) into various product matrices. However, the effect of pomace addition on extruded end-product sensory and nutritional qualities was observed to be highly variable depending on extrusion conditions, pre and postextrusion treatments, source of byproducts, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the results constitute evidence of an appreciable presence of NEPP in plant foods and of their contribution to total polyphenol intake. (31) Quince 48 (32) Banana 980 (SD 45)* (27) Apple pomace 18 -23 (33) Cranberry pomace 1685 (34) Cocoa powder 602 (SD 13) (35) Carob pod 180 (36) Hydrolysable phenolics Onion 410 (SD 20)* (37) Black olive 14 -40 (38) Apple 78 (SD 6) (29) Medlar 0·5 -1·0 (39) Mandarin 39 -107 (40) Acerola 390 (SD 10)* (41) Cashew apple 1210 (SD 70)* † (41) Black currant pomace…”
Section: Occurrence Of Non-extractable Polyphenols In Dietsmentioning
confidence: 99%